Experience of Mothers about their Infants' Teething in Mosul City - Ghada Dh Al-Sayagh; Baydaa A Al-Rawi; Ghaeth H Yassen (University of Mosul, College of Dentistry, 2008)
Aims: To evaluate mothers experience about their infants' teething, which symptoms they have seen and attributed to teething and how they have acted to manage these symptoms. Material and Methods: In this study, A total of 200 mothers of children less than 18 months of age, who had at least one tooth and who came to the primary health care centers for vaccination of their children were asked to participate in this study. The first part of the questionnaires was to clarify the eruption time of the first primary tooth and in the other part the mothers were also asked about the symptoms they attributed to teething and the methods they used to relief the symptoms. Results: The mean eruption time of the first tooth of the infants was 6.9 ± 2 months, with a range of 4 - 18 months. All of the mothers reported that their children had suffered from at least one of the symptoms that were mentioned in the questionnaire. The prevalence of teething symptoms distributed according to the age groups demonstrated that fever, irritability, sleep disturbance and lose of appetite were significantly highest in (below 6) months age group, while diarrhea, dribbling, runny nose, vomiting, cough, diaper rash and smelly urine were significantly highest in (6 - 12) months age group. Conclusion: It is commonly thought that teething in infants can cause a variety of signs and symptoms. In this study all the mothers believed that teething is associated with the appearance of symptoms, some of which are minor and related to discomfort, while others are physical illness